2012
DOI: 10.1016/j.apsusc.2012.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and elevated-temperature erosion-oxidation behaviour of aluminized 9Cr-1Mo Steel

Abstract: Degradation of materials by a combination of erosive wear and atmospheric oxidation at elevated temper-atures constitutes a problem in some power generation processes, such as fluidized-bed combustion. In this work, 9Cr-1Mo steel, a common tube material in combustion chambers, is coated by a pack cemen-tation method from an Alcontaining pack in order to improve the resistance to erosion-oxidation at elevated temperatures. The resulting coating is studied in terms of microstructure and microhardness and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Secondly, the packing activator of NH 4 Cl would also induce inward diffusion of N in the coatings. Thirdly, AlN exhibits a large negative Gibbs free energy of formation, i.e., −287 kJ mol −1 [24], which facilitates its formation where Al and N are sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the packing activator of NH 4 Cl would also induce inward diffusion of N in the coatings. Thirdly, AlN exhibits a large negative Gibbs free energy of formation, i.e., −287 kJ mol −1 [24], which facilitates its formation where Al and N are sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…An SEM/EBSD investigation has also been performed on the slurry aluminised Super 304H samples exposed to steam oxidation conditions at 700 and 750uC, this revealed phase changes occurring because of the columnar growth associated with the Al enrichment of the substrate. In the literature, most of the reported microstructural studies have been carried out on aluminised ferritic (BCC) steels produced by hot dipping in molten aluminium, [11][12][13][14][15][16][17] hence no phase change would be expected to occur as a result of Al enrichment. Limited EBSD work carried out by Danzo et al 13 reported that columnar grains of Fe 2 Al 5 grew on the surface of ferritic steels after aluminising in a molten mixture of Al-1 wt-%Si at 700uC for 20 s.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminizing, including hot-dip aluminizing [8], pack cementation aluminizing [9,10], and reactive air aluminizing (RAA) [11], is often used to hinder the oxidation process by facilitating the formation of a thermodynamically stable thin layer of Al 2 O 3 . Therein, pack cementation is a cost-effective and promising technique to achieve diffusion coatings with a stable structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, pack cementation is a cost-effective and promising technique to achieve diffusion coatings with a stable structure. For instance, Saarivirta et al [9] fabricated the 9Cr-1Mo Steel with Al-rich coating by pack cementation, and demonstrated that the presence of hard AlN precipitates in coating improved the resistance against erosion-oxidation of the steel specimens. Prasetya et al [10] prepared carbon steel by pack cementation with Al and Cr, respectively, and found that the growth of oxide scale was inhibited by Al coating, but not restricted by Cr coating.…”
Section: Introductionmentioning
confidence: 99%